Dasycladalean green algae and some problematic algae from the Upper Triassic of the Nayband Formation (northeast Iran) - Senowbari-Daryan, Baba; Rashidi, Koorosh; Saberzadeh, Behnam (Geologica Carpathica, 2011)
This paper describes the dasycladales green algae from two sections of the Rhaetian Howz-e Khan Member of the Nayband Formation, northwest of the Dig-e Rostam motorway service area (south of the type locality of the Formation near the town Naybandan). Both sections are composed of bedded fine-grained limestones containing partly abundant dasycladales algae associated with foraminifers, which are mainly aulotortid types. Additionally scattered samples were collected from several beds of the Howz-e Khan Member in this area. The following dasycladalean taxa are described: Chinianella carpatica (Bystrický), Griphoporella curvata (Gümbel), Griphoporella lutensis nov. sp., some undetermined dasycladacean taxa, problematic algae like Lithocodium aggregatum Elliott, Bacinella irregularis Radoicic, and Thaumatoporella parvovesiculifera (Raineri). While Chinianella carpatica is not numerous and the other described algae are rare, Griphoporella curvata is extremely abundant in the investigated material. This paper describes Ch. carpatica for the first time from the Triassic of Iran and also includes a discussion of the strong variability of G. curvata. Additionally we include an informal description of a problematic fossil (animal: shell fragment?; plant: alga?).
UnivIS-Import:2017-11-07:Pub.2011.nat.dgeo.IGM.LP.dasycl
Keywords: Bacinella; Chinianella; Dasycladales; Green Algae; Griphoporella; Gyroporella; Iran; Lithocodium; Nayband Formation; Triassic